2010
DOI: 10.3109/00365548.2010.485575
|View full text |Cite
|
Sign up to set email alerts
|

Screening for latent tuberculosis infection in South Korean healthcare workers using a tuberculin skin test and whole blood interferon-γ assay

Abstract: This study compared the results of a tuberculin skin test (TST) and a whole-blood interferon-gamma release assay (IGRA) to screen latent tuberculosis (TB) infection (LTBI) according to risk of TB exposure in South Korea. A cross-sectional comparison of 82 healthcare workers (HCWs) was performed from June 2009 to January 2010. Participants were grouped according to their risk for TB exposure: group 1, frequent and direct contact with active TB patients (n = 35); group 2, no known history of direct contact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
5
19
0
Order By: Relevance
“…Our study showed poor agreement between the TST and the QFT-GIT, which is consistent with previous reports6,12. In South Korea, where BCG vaccination is mandatory, children are vaccinated with BCG at birth; until 1997, TST non-responders were revaccinated again at age 12 or 13 years13.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our study showed poor agreement between the TST and the QFT-GIT, which is consistent with previous reports6,12. In South Korea, where BCG vaccination is mandatory, children are vaccinated with BCG at birth; until 1997, TST non-responders were revaccinated again at age 12 or 13 years13.…”
Section: Discussionsupporting
confidence: 89%
“…The statistically significant association between the experience of working in TB-related departments and a positive LTBI result on QFT-GIT and not on TST in our study supports the above hypothesis. This assumption was also made in previous studies which were conducted in South Korea6,9,12 as well as in other countries4,14,15. Moreover, while the positive rate of the TST in the present study was not different from that in the general population, the positive QFT-GIT rate was significantly higher than that in general population in South Korea (unpublished data).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations